TRCirc: a resource for transcriptional regulation information of circRNAs. (3rd September 2018) - Tang, Zhidong; Li, Xuecang; Zhao, Jianmei; Qian, Fengcui; Feng, Chenchen; Li, Yanyu; Zhang, Jian; Jiang, Yong; Yang, Yongsan; Wang, Qiuyu; Li, Chunquan
Abstract: In recent years, high-throughput genomic technologies like chromatin immunoprecipitation sequencing (ChIp-seq) and transcriptome sequencing (RNA-seq) have been becoming both more refined and less expensive, making them more accessible. Many circular RNAs (circRNAs) that originate from back-spliced exons have been identified in various cell lines across different species. However, the regulatory mechanism for transcription of circRNAs remains unclear. Therefore, there is an urgent need to construct a database detailing the transcriptional regulation of circRNAs. TRCirc (http://www.licpathway.net/TRCirc ) provides a resource for efficient retrieval, browsing and visualization of transcriptional regulation information of circRNAs. The current version of TRCirc documents 92 375 circRNAs and 161 transcription factors (TFs) from more than 100 cell types and together represent more than 765 000 TF–circRNA regulatory relationships. Furthermore, TRCirc provides other regulatory information about transcription of circRNAs, including their expression, methylation levels, H3K27ac signals in regulation regions and super-enhancers associated with circRNAs. TRCirc provides a convenient, user-friendly interface to search, browse and visualize detailed information about these circRNAs.